How Do EFL Teachers Navigate Problem-Based Learning in Indonesian Classrooms? - Azzahra, Nurfie Rahmadani; Nurkamto, Joko (VELES Voices of English Language Education Society, 2024)
The adoption of Problem-Based Learning (PBL) in English language education is gaining momentum due to its potential to enhance students' language proficiency, critical thinking, and problem-solving skills, which are essential for the 5.0 society era. Despite its numerous benefits, the implementation of PBL in secondary English education remains limited, primarily due to the complexities of designing instructional plans that align with student-centered learning curricula. This study investigates teachers’ competence in developing PBL lesson plans and explores their challenges. Using a case study approach, the research focuses on four in-service English teachers with extensive experience and pedagogical expertise. Guided by the framework of social constructivism, data were collected and analyzed thematically. The findings reveal the current state of teacher preparedness and highlight key contextual challenges, including managing diverse student competencies and characteristics, addressing classroom management issues, and effectively utilizing digital technology in instruction. These challenges emphasize the need for systemic support, professional development opportunities, and policy reforms that prioritize enhancing pedagogical practices over mere compliance. Addressing these issues is critical for fostering productive and supportive PBL learning environments in English language education.